Football, Fascism and Fandom in Modern Italy - Martin,Simon (2018)
This paper will examine the relationship between Fascism and football in Italy from the regime's origins in the mid-1920s through to the present day and will seek to explain the far right's continued presence in the game. Contextualising Italian football's development within the nation's postwar history, it will argue that while the Fascist regime laid the foundations of the contemporary game, its influence was not profound enough to explain the far-right's existence in Italian stadiums since the 1980s. By situating the politicisation of Italian football within theories of post-Fascist memory and via the examination of specific incidents of pro-regime and anti-Semitic activity within the stadiums, this paper will argue that the failure to combat the far-right's presence has been a direct consequence of the weakness/absence of the Italian state.